Adult Education and Spirituality: A "Liberatory Spaces" for Black Gay Men. Issue 150 (June 2016) - Bryant, Lawrence; Bowman, Lorenzo; Paulette Isaac‐Savage, E.
Abstract : In this chapter the authors examine the role of spirituality in the lives of Black gay men.